(untitled) (Global Journal of Human-Social Science, 2025)
This article aims to analyze agroecology in metropolitan regions in Brazil, based on the concepts of socio-spatial and socio-territorial movements. It also draws parallels regarding the presence of agroecology in different metropolitan regions. Another aspect is to continue evaluating these concepts to understand the dynamics of agroecology. The method relies on primary sources from previous research and secondary sources for data comparison. As concluding considerations, the advancement of agroecology depends on the conquest of land and territory -stemming from socio-territorial movements -and on its spatial dissemination, where socio-spatial movements may have an impact. While socio-territorial movements are necessary for agroecology, they are not sufficient on their own. In this case, the concept of socio-territorial movement is explanatory. The expansion of agroecology in metropolitan regions is driven by the actions of movements, associations, and universities. This is a socio-spatial action, such as networks, not merely the presence of socio-spatial movements.